The Effect of InGDEP on Type 2 Diabetes Patients’ Knowledge and Self-Care - Hema Malini; Fitra Yeni; Dilya Eka Saputri (Jurnal Keperawatan Padjadjaran, 2018)
In the recent years, there is an increasing number of the diabetes incidence worldwide. Self-care is believed as one of key in chronic disease management. In order to increase the capability to self-care, diabetics patients need to be empowered with the knowledge and skills through an educational program. There were some existed diabetes educational programs, however for developing country such as Indonesia, there was a need to develop a culturally relevant diabetes education program. This study was aimed to identify feasibility and the effect of the Indonesian Group-based Diabetes Education Program (InGDEP) on knowledge and self-care behaviors among type 2 diabetic patients. This quasi experimental with one group pre-and post-test only design involved 62 diabetic patients and 16 health professionals who actively delivered the program in four community health centers (Puskesmas). Data were collected using Diabetes Knowledge Questionnaire (DKQ) and Summary of Self Care Activities (SDSCA). Paired t-test used to analyze the effect of the InGDEP on the knowledge, self-care, and biometric measurement (HbA1c). The knowledge score for pre-test was 13.2+3.9 and post-test was 16.1±3.5, self-care activities score for pre-test was 3.31±1.10 and post-test was 3.99±1.27 and the HbA1C level was 10.56±2.32 The results showed there was the significant effect of InGDEP on diabetes patients’ knowledge, some changes in self-care and biometric measurements even though it was not significant. The program also can be accepted by the health professionals where there was a good team work in delivering the educational program. It can be recommended that the InGDEP has an effect in improving knowledge and self-care among diabetics’ patients, however since the effect on self-care and biometric changes was not significant, further research related to the factors that influence the self-care and biometric changes is needed.